A Mobile application for tracing and verification of the authenticity of filled liquefied petroleum gas cylinders - Mutua, Carolyne Wanza (2017)
Tracing and verification of the authenticity of filled Liquefied Petroleum Gas (LPG) cylinders has been marked with numerous challenges especially in the Sub-Saharan region. With an increase in LPG consumption, numerous sales points have sprouted in residential estates which even sell unbranded cylinders. Some traders involved in the illegal refilling and branding of cylinders use cylinders that do not meet the quality standards of the Kenya Bureau of Standards, thus compromising consumers' safety. Consequently, unlicensed gas operators are gaining an unfair advantage as they do not incur the cost of purchasing cylinders. Consumers end up paying the same for genuine and illegal products in spite of the non-compliance on safety checks, cylinder re-validation, gas specifications, quantity and value added tax remittance. This research used document survey and an online questionnaire that was distributed to 96 LPG consumers to provide a detailed study of the characteristics of the authenticity of a filled LPG cylinder, methods and technology currently used to trace and verify the authenticity of filled LPG cylinder and how a mobile application for tracing and verification of the authenticity of filled LPG cylinder can be designed, developed, tested and validated. The data collected from the 96 respondents was analysed using Google analytics tools and the results used to obtain the system requirements and design of an Android mobile application for tracing and verifying the authenticity of filled Liquefied Petroleum Gas cylinders. Agile software development methodology was used which allows faster iteration and more frequent user feedback. The Android application was integrated with an analytical back-end for LPG manufacturers, distributors and retailers that present a summary of LPG supplies made. Testing and validation was done on the final prototype by the potential users and developer of the application. Users stand to benefit by using the mobile application to ensure their safety by verifying the authenticity of gas cylinders anytime and from anywhere.
Printout.
Thesis ()--Oregon State University, .
Also available on the World Wide Web.
Includes bibliographical references (leaves - ).
Keywords: Filled Liquefied Petroleum -- Gas Cylinders; Cylinder Identifiable; QR Code; Bar Codes